Surfactant biodegradation in batch reactors with aspergillus niger AN400. (8th May 2019) - Marinho, Gloria; Cavalcante, F. Reinaldo; Silveira, Renata Brasil; Pereira, Luciana; Barbosa, Bárbara; Rodrigues, Kelly
The wide production and use of the surfactant linear alkylbenzene sulphonate (LAS) has severe effects on the environment and, consequently on human health. This study sought to evaluate the efficiency of the species aspergillus niger AN400 on LAS removal, in reactors operated in batch mode. Three reactors were operated for 30 days with the following configuration: a control reactor without A . niger AN400 (CR) and two reactors with A . niger AN400, one of each supplemented with 1 mg L −1 of glucose (ANGR) and one without the co-substrate (ANR). LAS was tested in the concentrations of 15 and 30 mg L −1 . LAS removal efficiencies 51% in ANR and 76% ANGR, for the initial concentration of LAS of 15 mg L −1, and 55% in ANR and 65% in ANGR, for 30 mg L −1 of LAS.